2021
DOI: 10.3171/2020.9.spine201395
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of nonoperatively managed degenerative cervical myelopathy: an ambispective longitudinal cohort study in 117 patients

Abstract: OBJECTIVE Degenerative cervical myelopathy (DCM) is among the most common pathologies affecting the spinal cord but its natural history is poorly characterized. The purpose of this study was to investigate functional outcomes in patients with DCM who were managed nonoperatively as well as the utility of quantitative clinical measures and MRI to detect deterioration. METHODS Patients with newly diagnosed DCM or recurrent myelopathic symptoms after previous surgery who were initially managed nonoperatively wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Each of the proposed scales provides another aspect of assessment and means to follow patients both pre and postoperatively. However, in general, it is believed that DCM is reasonably well followed with the mJOA in conjunction with objective testing of DCM patients with examination of myelopathic signs and objective measures of grip strength, dexterity, balance, and gait [31,32]. As such, most recommendations for determining severity of DCM in patients and clinical decision making primarily utilize mJOA.…”
Section: Normal Urinary Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Each of the proposed scales provides another aspect of assessment and means to follow patients both pre and postoperatively. However, in general, it is believed that DCM is reasonably well followed with the mJOA in conjunction with objective testing of DCM patients with examination of myelopathic signs and objective measures of grip strength, dexterity, balance, and gait [31,32]. As such, most recommendations for determining severity of DCM in patients and clinical decision making primarily utilize mJOA.…”
Section: Normal Urinary Functionmentioning
confidence: 99%
“…Martin et al suggested that the primary purpose of MRI in DCM is to establish the diagnosis and for surgical planning. In their longitudinal study of DCM patients, MRI had a sensitivity of only 28% in detecting clinical deterioration of DCM and should not be relied upon as a measure to follow DCM patients [32]. Martin et al suggested that the primary purpose of MRI in DCM is to establish the diagnosis and for surgical planning.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, recent work suggests that >50% of patients with mild-moderate DCM will decline over a 2.5year follow-up period and that conventional magnetic resonance imaging (MRI) techniques are insensitive to detect this change. 8 Quantitative MRI (qMRI) techniques can provide biomarkers sensitive to spinal cord tissue integrity 9 and underlying pathology in DCM 7,10 and help in clinical decision making (i.e., early surgery vs. conservative treatment).…”
Section: Introductionmentioning
confidence: 99%
“…The reliance on these outcome measures has increased to the point that clinical practice guidelines (CPGs) published by AOSpine are based on the mJOA alone, recommending surgery for moderate-severe cases and mild cases that show progressive deterioration [ 4 ]. However, reliance on the mJOA is problematic in several ways, as scores can be affected by other medical conditions, interobserver reliability is limited [ 5 , 6 ], and it remains unclear how to best assess patients for neurological deterioration, although comprehensive clinical assessments and quantitative microstructural MRI have been proposed [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%